Urban snowmelt and runoff in northern Sweden - Bengtsson, Lars; Westerström, Göran (Hydrological Sciences Journal, 1992)
Snowmelt and runoff in urban areas in Lulea, north Sweden, are discussed and compared with rural conditions. The uneven snow distribution in cities is quantified. Energy fluxes at the snow surface in different environments are estimated. It is shown that, mainly because of increased absorbed radiative energy in the snow, the daily melt is about 10 mm higher in the city than in rural environments. In the course of prolonged snowmelt, the infiltration capacity of most soils in urban areas becomes so reduced that melt-induced peak flows from grassed and gravelled surfaces are similar to those from asphalted surfaces. When rain falls on snow, overland flow may take place from the entire area of a basin Godkänd; 1992; 20090311 (andbra)